Deep brain stimulation for neuropathic pain. - Owen, S; Green, A; Nandi, D; Bittar, R; Wang, S; Aziz, T (2006)
Objectives.  To determine whether deep brain stimulation is an effective treatment for neuropathic pain of varied etiology. Material and Methods.  Thirty-four patients with intractable neuropathic pain were prospectively studied using visual analog scores, McGill Pain Questionnaire, and Quality of Life Questionnaires (EUROQOL EQ-5D VAS, and SF-36 v-2). Patients had either deep brain stimulation of either the periventricular gray or ventroposterolateral nucleus of the thalamus, or both. Results.  Seventy-six percent of patients underwent permanent implantation. Overall reduction of pain intensity was 54%. The burning component of pain improved by 77%. Health-related quality of life improved by 38%. Conclusions.  Deep brain stimulation is an effective treatment for neuropathic pain. The factors that influence outcome, including etiology and site of stimulation, are discussed.